Macroeconomic foundations and simulation properties of the BOF4 quarterly model of the Finnish economy - Juha Tarkka; Hanna-Leena Männistö; Alpo Willman (Bank of Finland, 1990)
This paper describes the structure and simulation properties of the Bank of Finland's macroeconometric model BOF4. BOF4 is a quarterly, medium-sized macro model of the Finnish economy, consisting of about 70 behavioural equations. Including accounting identities and technical linkages of variables, the overall size of the model is about 270 equations. It replaced the previous (BOF3) model version in 1987, and has been used regularly thereafter for forecasting and policy analysis.
URN:NBN:fi:bof-201807311789
Keywords: 330